Experimental Study on the Incipient Movement of Muddy Clay under Different Salinity Conditions - Xiaolei Zhang; Xin Liu; Haoran Wu; Shuyu Liu; Yu Zhu; Zhengzheng Bi; Zhiheng Xu (The Scientific World Journal)
In order to understand the incipient movement of muddy clay under different salinity conditions, three series of flume tests were performed on incipient movement of muddy clay, including tests on incipient movement of salt-free clay mud under salt water conditions (salt water-salt-free clay mud), incipient movement of salt clay mud under salt water conditions (salt water-salt clay mud), and incipient movement of salt clay mud under freshwater conditions (freshwater-salt clay mud), using a circulating flume, in which the salinity of the water body or cohesive sediment varies from 0 to 40%. Based on the particle image velocimetry system and digital image gray processing technology, the gray curves of water near the clay mud bed surface with the velocity were plotted to quantitatively differentiate the incipient velocity of the sediment for each test. The experimental results showed that the higher the salinity of the water body or cohesive sediments is, the more difficult it is to start moving. There is a logarithmic relationship between the incipient velocity of cohesive sediments and the salinity of the water or cohesive sediments. The incipient velocity increases sharply at a salinity of 0∼10% and slowly at a salinity of 10∼40%. At the same salinity, the incipient velocity of salt clay mud under freshwater conditions is the largest, followed by that of salt clay mud under salt water conditions, while that of salt-free clay mud under salt water conditions is the smallest. In addition, the flow turbulence characteristics were analyzed under the critical conditions of the onset of muddy clay. Ultimately, an empirical formula to calculate the critical incipient velocity of muddy clay is proposed by introducing the salinity. In this study, salinity is included as a reference variable, which expands the research scope of sediment initiation and provides a reference for the study of estuary dynamics.